2022
DOI: 10.3390/ma15031218
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution of Graphene and the Corresponding Effect on the Mechanical/Electrical Properties of Graphene/Cu Composite during Rolling Treatment

Abstract: Rolling enables the directional alignment of the reinforcements in graphene/Cu composites while achieving uniform graphene dispersion and matrix grain refinement. This is expected to achieve a breakthrough in composite performance. In this paper, the process parameters of rolling are investigated, and the defects, thickness variations of graphene and property changes of the composite under different parameters are analyzed. High-temperature rolling is beneficial to avoid the damage of graphene during rolling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, the intensity ratio of the peaks can only reflect the change in D peak intensity. We have, therefore, used the area ratio of the D-to-G peak (I D /I G ) to describe the change in graphene defect density, which has also been reported in other studies [ 10 , 21 ]. To accurately estimate this ratio, Gauss–Lorentz area numerical integration has been used to fit the D and G peaks.…”
Section: Resultsmentioning
confidence: 99%
“…However, the intensity ratio of the peaks can only reflect the change in D peak intensity. We have, therefore, used the area ratio of the D-to-G peak (I D /I G ) to describe the change in graphene defect density, which has also been reported in other studies [ 10 , 21 ]. To accurately estimate this ratio, Gauss–Lorentz area numerical integration has been used to fit the D and G peaks.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that the cold-rolling treatment in this research with large deformations exceeding 80% surprisingly contributes to improve the mechanical and electrical properties of graphene/copper composites. However, significant performance degradation occurs in the cold-rolled composite fabricated with ball milling, with similar deformation [24]; the hardness of the cold-rolled composite with 80% deformation is only…”
Section: Mechanical and Electrical Properties Of Composites Under Dif...mentioning
confidence: 99%
“…The composite with 80% rolling reduction rolled at 500 ℃ was shown to have a maximum ultimate strength of 441 MPa. Xiu et al investigated the effects of rolling temperature and deformation on the graphene microstructure and composite performance in a 0.6 wt.% graphene/copper composite [ 24 ]. The results showed that high-temperature rolling contributes to avoiding damage to graphene during rolling and improving the properties of the composites.…”
Section: Introductionmentioning
confidence: 99%